Improving Thematic Learning Outcomes Of My Daily Task Subthema At Home Using The Make A Match Type Cooperative Learning Model In Class Ii Students Of SDN 019 Tanjung Sawit, Tapung District - Syaiful, Noverlinda (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The method used in this classroom action research is the Kurt Lewin model which contains 4 (four) stages, namely planning, action, observation and reflection. The subjects in this research were class II students at SDN 019 Tanjung Sawit, consisting of 26 students. Data collection was carried out by researchers through observation, interviews, tests and documentation. The research results show that: 1) Implementing the Make a Match type cooperative model can increase teacher and student activity. The results of observing teacher activities in cycle I were 72.52, and increased to 90.32 in cycle II. Meanwhile, the results of observing student activities in cycle I were 70.83, and increased to 91.7 in cycle II. 2) The increase in student learning outcomes can be seen from the average score of Indonesian language subject students in the pre-cycle of 63.7 with a percentage of 46.15%, in the first cycle it was 72.7, with a percentage of 69.23%, and increased to 77, with a percentage of 80.8% in cycle II.